Efecto de regímenes de anticipos de impuestos en capacidad de pago y rentabilidad de empresas del sector de construcción - Diego Fano; Gabriel Oubi\~na; Saverio Di Giorgio; Antonio Marín (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2018)
– Argentina is known for its tax system, that has various mechanisms to collect taxes in advance, causing large immobilizations in illiquid tax credits in most companies. The objective of this paper is to analyze the effects that these tax advances regimes would generate on the payment capacity and financing needs of companies that belongs to the construction sector, which are characterized by long productive cycles and long time for assets collection. To this end, the financial statements of forty-seven companies belonging to this sector were studied between 2004 and 2016, in relation to the proportion of tax credits over assets, payment ratios, financing needs through loans and levels of profitability. It was observed that at higher levels tax credits immobilization, payment ratios decreased rapidly, as also greater use of financial liabilities (loans) were needed for financing them, which would result in higher financial costs to sustain than immobilization. That phenomenon is worse on those companies with lower levels of profitability. These findings would allow to conclude the harmful effect of the advance tax regimes for undermining the competitiveness of companies and their capacity for development and investment.
Keywords: 330; Steuersystem; Bauwirtschaft; Unternehmensbesteuerung; Befolgungskosten; Betriebliche Liquidität; Unternehmensfinanzierung; Argentinien